Gaya Bahasa Perbandingan dalam Lirik Lagu Album Selamat Ulang Tahun dan Kalah Bertaruh Karya Nadin Amizah - Vita Setiawati; Albertus Purwaka; Lazarus Linarto; Alifiah Nurachmana; Muh Muslim; Rahmat Syakur (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The aim of this research is to describe (1) the type of comparative language style found in the lyrics of the album Selamat Birthday dan Kalah Berbet by Nadin Amizah, (2) The function of the comparative language style found in the lyrics of the album Happy Birthday and Lose Bet by Nadin Amizah. This research is a qualitative descriptive study. The data source in this research is the lyrics of the album Happy Birthday and Lose Betting by Nadin Amizah. The data in this research is in the form of types and functions of comparative language styles contained in the lyrics of the album Happy Birthday and Losing Bets by Nadin Amizah with the form of data in the form of words, phrases, clauses and sentences contained in lines and verses in the lyrics of the album Happy Birthday and Losing Bets by Nadin Amizah which deals with the types and functions of comparative language styles. Data collection techniques were carried out using library techniques, listening, taking notes and entering them into data cards. Data analysis uses qualitative content analysis techniques. Based on the results of the analysis, it can be concluded that in the lyrics of the album Happy Birthday and Losing Bets by Nadin Amizah, there are types and functions of comparative language styles used by the author in the album's song lyrics. The types of comparative language styles found in the lyrics of the album Happy Birthday and Lose Betting by Nadin Amizah are in the form of similes, metaphors, personification, depersonification, allegory, antithesis, pleonasm, periphrasis, prolepsis or anticipation, and correction or epanorthosis., while the function of language style The comparisons contained in the lyrics of the album Happy Birthday and Losing Betting by Nadin Amizah are in the form of information function, expressive function, aesthetic function, directive function and phatic function.